2006
DOI: 10.1002/gps.1703
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of older adults with co‐morbid personality disorder and depression: a dialectical behavior therapy approach

Abstract: Results from these two treatment development studies indicate that applying standard DBT for the treatment of co-morbid MDD or MDD + PD in older adults is feasible, acceptable, and has clinical promise. Modifications to standard DBT and an overview of a new treatment manual for this population are summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(105 citation statements)
references
References 58 publications
3
89
0
13
Order By: Relevance
“…Given that this census-based sample found that 1 in 10 older adults were characterized by a profile of histories of serious suicidal ideation/behavior in the absence of current psychological distress other than recent death wishes, research is needed to examine the potential benefits of regular screening of suicide risk among all older adults, not just those with depression. Research is also needed regarding clinical management of those older adults presenting with death wishes in the absence of significant depression—specifically, whether treatments shown to be effective for older adults with suicidal ideation and depression 3133 are useful and whether treatments targeting factors other than depression (e.g., targeting loneliness 34 ) are also useful.…”
Section: Discussionmentioning
confidence: 99%
“…Given that this census-based sample found that 1 in 10 older adults were characterized by a profile of histories of serious suicidal ideation/behavior in the absence of current psychological distress other than recent death wishes, research is needed to examine the potential benefits of regular screening of suicide risk among all older adults, not just those with depression. Research is also needed regarding clinical management of those older adults presenting with death wishes in the absence of significant depression—specifically, whether treatments shown to be effective for older adults with suicidal ideation and depression 3133 are useful and whether treatments targeting factors other than depression (e.g., targeting loneliness 34 ) are also useful.…”
Section: Discussionmentioning
confidence: 99%
“…Por tanto, se excluyeron estudios de caso, teóricos, metodológicos, correlacionales, cualitativos y/o protocolos experimentales sin muestra clínica. Se excluyeron del presente análisis el estudio de Lych, Morse, Mendelson y Robins (2003) y el de Gallagher y Thompson (1983) por presentar datos parcialmente repetidos (véase Gallagher y Thompson, 1982;Lynch et al, 2007). Figura 1.…”
Section: Métodounclassified
“…Dos ensayos clínicos aleatorizados demostraron también que la TDC generó disminución en el consumo de sustancias (29,45). Un estudio conducido por Lynch en el 2007, encontró efectos positivos de la TDC estándar en depresión en adultos mayores (46). Harned en el 2010 realizó un ensayo Reducir y eliminar conductas que atentan contra la vida.…”
Section: Rev Neuropsiquiatr 79 (2) 2016unclassified